Menerangi Tradisi Melalui Inovasi: Transformasi Wisata Tenun Tradisional dalam Pariwisata Cerdas di Kabupaten Lombok Tengah - Fitri, Suci Emilia; Pranasari, Melati Ayuning; Indarti, Dian Martha; Savira, Evi Maya; Andari, Tania; Aprilani, Triana Lidona; Utami, Karina Juniarti; Putri, Nadia; Manoby, Worry Mambusy; Putra, Imam Radianto Anwar Setia; Saksono, Herie (Jurnal Bina Praja, 2023)
This study aims to explore the challenges that have long hindered the progress of traditional weaving tourism in Central Lombok Regency and unravel the role of innovation as a breakthrough and solution. The study's focus centered on the importance of innovation as a transformative factor for traditional weaving tourism within the framework of smart tourism in Lombok Tengah Regency. It is known that the distinctive traditional weaving of Lombok has a long history and is an integral part of local life and culture, passed down through generations. However, realistically, traditional weaving must contend with challenges such as the low prices of woven fabric products, the lack of interest among the younger generation to learn weaving, and the limited capacity of weavers to respond to local, domestic, and even global market demands. This study employs a qualitative-exploratory approach, with the research taking place in the villages of Rembitan and Sukarara in Lombok Tengah Regency. The study finds that the challenges faced by traditional weaving can only be overcome through innovation. Innovation has the ability to overcome various obstacles by developing products and creating new designs that align with tourists' interests, utilizing digital technology to market and sell traditional woven products, imparting new skills and techniques to weavers, and promoting traditional weaving as a cultural heritage through digital platforms. Innovation has successfully transformed the traditional weaving tourism industry, even though this transformation is still partial. The dodeca-helix approach within the Tourism Hub can synergize stakeholders to create innovation for transforming the industry despite challenges that must be overcome for this transformation to materialize. In the effort to change the traditional weaving tourism industry through innovation, it is recommended that the Government, private sector, and local community collaborate to address challenges and create innovations to guide the development of traditional weaving in the future.